Aerodynamic analysis and control for a novel coaxial ducted fan aerial robot in ground effect - Tianfu Ai; Bin Xu; Changle Xiang; Wei Fan; Yibo Zhang (International Journal of Advanced Robotic Systems, 2020)
Modeling and control for a novel coaxial ducted fan aerial robot in-ground-effect is presented in this article. Based on experiments using the ducted fan bench test, the fitting curve of the ground effect thrust of the ducted fan aerial robot at different heights is obtained. In addition, the flow field simulation results of the prototype with ground effect at different heights can be obtained using computational fluid dynamics software. A simplified model of the prototype for control can be designed based on several reasonable hypotheses that are established using blade element and momentum theory. To compensate for the disturbance associated with ground effect, a nonlinear disturbance observer is designed to estimate the disturbance, and control structure of the closed-loop system is composed of a nonlinear disturbance observer combined with a double-loop proportion–integration–differentiation controller. The results of several numerical simulations and experiments demonstrate the effectiveness of this controller structure. The performances of tracking trajectory and system stability are improved significantly, compared to the situation that the ground effect is not compensated for.